Between adoption and refusal : european objects at Vilcabamba, the last stronghold of the inca resistance (1537-1572) - Merry, Alice Kate (2021)
Vilcabamba was the site of the final stronghold of the Inca resistance for nearly forty years from 1537 until 1572. Though it has often been thought of as an isolated region during this period, interactions between the Inca and Spanish play an important part in its history. This thesis explores how these interactions are reflected in the material culture of Vilcabamba, by examining European and European-style objects at Vilcabamba, including glass objects; scissors; other metal objects such as nails, latches, hinges and tools; tiles; and ceramics. These objects are analysed on the basis of both archaeological and historical evidence, including documentation of explorations and excavations conducted at Vilcabamba, from Hiram Bingham’s first explorations of the site in 1911 to recent excavations conducted from 2008 to 2010 by Javier Fonseca Santa Cruz and by Brian S. Bauer and Miriam Aráoz Silva, as well as the chronicles of Antonio Bautista de Salazar (1867 [1596]), Martín de Murúa (2008 [ca. 1616]), Baltasar de Ocampo Conejeros (2013 [1611]), and Diego Rodríguez de Figueroa (1910 [1565]). From a Spanish perspective, European objects brought to Vilcabamba represented careful gift-giving as part of delicate diplomatic negotiations. On the Inca side, selected European objects were actively adopted and incorporated into the most important elite and ritual settings at Vilcabamba. This thesis argues that these objects were used to create new cultural phenomena that spoke to the strategies and ideologies of the Inca at Vilcabamba.